Access to and affordability of CAR T-cell therapy in multiple myeloma: an EBMT position paper. Issue 10 (October 2022) - Gagelmann, Nico; Sureda, Anna; Montoto, Silvia; Murray, John; Bolaños, Natacha; Kenyon, Michelle; Beksac, Meral; Schönland, Stefan; Hayden, Patrick; Scheurer, Hans; Morgan, Kate; Garderet, Laurent; et al.
Summary: Chimeric antigen receptor (CAR) T-cell therapy is a promising immunotherapeutic approach in the treatment of multiple myeloma, and the recent approval of the first two CAR T-cell products could result in improved outcomes. However, it remains a complex and expensive technology, which poses challenges to health-care systems and society in general, especially in times of crises. This potentially accelerates pre-existing inequalities as access to CAR T-cell therapy varies, both between countries, depending on the level of economic development, and within countries, due to structural disparities in access to quality health care—a parameter strongly correlated with socioeconomic status, ethnicity, and lifestyle. Here, we identify two important issues: affordability and access to CAR T-cell treatment. This consensus statement from clinical investigators, clinicians, nurses, and patients from the European Society for Blood and Marrow Transplantation (EBMT) proposes solutions as part of an innovative collaborative strategy to make CAR T-cell therapy accessible to all patients with multiple myeloma.